The Structure of the Asset Portfolios of Households - Uhler, R. S.; Cragg, J. G. (Review of Economic Studies, 1971)
R. S. Uhler, J. G. Cragg; The Structure of the Asset Portfolios of Households1, The Review of Economic Studies, Volume 38, Issue 3, 1 July 1971, Pages 341–